2019
DOI: 10.5607/en.2019.28.4.537
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of SIRT2 by Chronic Stress Reduces Expression of Synaptic Plasticity-related Genes through the Upregulation of Ehmt2

Abstract: Silent information regulator 2 (Sirtuin2 / SIRT2) is a NAD+-dependent deacetylase that regulates the cellular oxidative stress response. It modulates transcriptional silencing and protein stability through deacetylation of target proteins including histones. Previous studies have shown that SIRT2 plays a role in mood disorders and hippocampus-dependent cognitive function, but the underlying neurobiological mechanism is poorly understood. Here, we report that chronic stress suppresses SIRT2 expression in the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The effect of sirtuin (SIRT) 2 knockdown in the DG is similar to that of chronic stress, and both downregulate plasticity-related genes [ 63 ]. In addition, chronic stress reduces SIRT1 activity in mice, leading to depression-like behavior [ 64 ].…”
Section: Changes In Hippocampal Plasticity In Depressionmentioning
confidence: 99%
“…The effect of sirtuin (SIRT) 2 knockdown in the DG is similar to that of chronic stress, and both downregulate plasticity-related genes [ 63 ]. In addition, chronic stress reduces SIRT1 activity in mice, leading to depression-like behavior [ 64 ].…”
Section: Changes In Hippocampal Plasticity In Depressionmentioning
confidence: 99%
“…Firstly, stress response allows body adaptation. However, when stress is prolonged it has been shown to decrease synaptic plasticity [8], alter hippocampal volume [9,10] and neurotransmitters [11], and may lead to AD [12]. In particular, chronic stress is associated with increased Aβ deposits and hyperphosphorylated Tau [13].Oxidative stress (OS) and inflammation are deeply involved in age-related deleterious disorders.…”
mentioning
confidence: 99%
“…However, in the CUS model of depression, Sirt2 expression in the Hp decreased and was reversed by fluoxetine treatment [ 82 ]. Other authors also confirmed a decrease in hippocampal Sirt2 expression in mice subjected to the CUS and CRS procedures [ 83 ]. In contrast, our study showed an increase in Sirt2 protein level in the Hp and a decrease in the PFC.…”
Section: Discussionmentioning
confidence: 66%